2013
DOI: 10.1373/clinchem.2012.193342
|View full text |Cite
|
Sign up to set email alerts
|

The Biology of Brain Metastasis

Abstract: BACKGROUND:It is estimated that at least 200 000 cases of brain metastases occur each year in the US, which is 10 times the number of patients diagnosed with primary brain tumors. Brain metastasis is associated with poor prognosis, neurological deterioration, diminished quality of life, and extremely short survival. Favorable interactions between tumor cells and cerebral microvascular endothelial cells encourage tumor growth in the central nervous system, while tumor cell interactions with astrocytes protect b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 64 publications
(64 reference statements)
0
56
0
1
Order By: Relevance
“…Activated astrocytes were shown to be recruited to brain metastases (2). Moreover, we previously showed that paracrine signaling from brain-metastasizing melanoma cells contributes to reprogramming and activation of astrocytes in vitro (21).…”
Section: Melanoma Brain Metastases Instigate Astrogliosis and Neuroinmentioning
confidence: 99%
See 2 more Smart Citations
“…Activated astrocytes were shown to be recruited to brain metastases (2). Moreover, we previously showed that paracrine signaling from brain-metastasizing melanoma cells contributes to reprogramming and activation of astrocytes in vitro (21).…”
Section: Melanoma Brain Metastases Instigate Astrogliosis and Neuroinmentioning
confidence: 99%
“…Autopsy reports show that 75% of melanoma patients who died of this disease developed brain metastases, and the incidence of brain metastasis is rising (1). Brain metastases are currently incurable, and are associated with a dismal median survival of less than one year (2). Therefore, it is essential to identify factors that play a role during the earliest stages of the metastatic process that may allow preventive therapeutics following removal of the primary tumor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extra medullary blast crisis (BC) occurs in 7-10 % of chronic myeloid leukemia (CML) patients and the use of imatinib as first-line treatment has been related to CNS involvement because of the scarce ability to cross the blood brain barrier (BBB) ( Table 1) [13]. Considering the increasing incidence of cancer and the metastasis as the main cause of death with invasion of the neural niche as the ultimate step of the tumor cascade, the recognition of CNS niche and the understanding the CNS involvement in & N. Saki najmaldinsaki@gmail.com leukemias appear of essence in the devise of novel diagnostic and therapeutic approaches [14,15]. Therefore, in this paper we provide a description of the factors that are effective upon CNS niche involvement in lymphoid and myeloid leukemias (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…173,174 After intravasation and dissemination of cancer cells, the adhesion and the migration of tumor cells across the wall of the blood vessels formed by endothelial cells, are the key steps in the formation of brain metastases. 175 The successful inhibition of these steps might prevent the formation of these tumors.…”
Section: Activities Of Lignans On Melanomas Brain Metastasis Formationmentioning
confidence: 99%